Review of the Priocnemis hyalinata species-group (Hymenoptera: Pompilidae), with description of a new species from China - Loktionov, Valery M.; Lelej, Arkady S.; Xu, Zai-Fu (Zootaxa, 2017)
Eight species in the Priocnemis hyalinata species-group are reviewed. The species-group is recorded from Oriental Region for the first time, and one new species, Priocnemis (Priocnemis) yunnanensis Loktionov, Lelej & Xu, sp. nov. (China: Yunnan) is described and illustrated. The lectotype of Salius (Priocnemis) unicolor Gussakovskij is designated. The distribution of P. (P.) hyalinata (Fabricius), P. (P.) fennica Haupt and P. (P.) unicolor (Gussakovskij) is clarified and enlarged within Russia. Keys to species for males and females are given.